2016
DOI: 10.3390/nano7010001
|View full text |Cite
|
Sign up to set email alerts
|

Improving Powder Magnetic Core Properties via Application of Thin, Insulating Silica-Nanosheet Layers on Iron Powder Particles

Abstract: A thin, insulating layer with high electrical resistivity is vital to achieving high performance of powder magnetic cores. Using layer-by-layer deposition of silica nanosheets or colloidal silica over insulating layers composed of strontium phosphate and boron oxide, we succeeded in fabricating insulating layers with high electrical resistivity on iron powder particles, which were subsequently used to prepare toroidal cores. The compact density of these cores decreased after coating with colloidal silica due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 38 publications
0
6
1
3
Order By: Relevance
“…79 NS. The spectrum of Si 2p consisting of two peaks can be attributed to the C-Si bonding, located at the binding energy of about~103.053 eV and SiO 2 located at the binding energy of about~103.998 [48,49]. The spectrum of C1 s revealed that the amorphous carbon from C/SiO 2 NS sample represent the two possible bonds of carbon C O (~287.6 eV) with atomic percentage of 74.49% and C-Si (~283.3) with atomic percentage of 24.51%, respectively [73].…”
Section: Surface Characteristics Of the Synthesized Silica Nanosheetsmentioning
confidence: 99%
See 1 more Smart Citation
“…79 NS. The spectrum of Si 2p consisting of two peaks can be attributed to the C-Si bonding, located at the binding energy of about~103.053 eV and SiO 2 located at the binding energy of about~103.998 [48,49]. The spectrum of C1 s revealed that the amorphous carbon from C/SiO 2 NS sample represent the two possible bonds of carbon C O (~287.6 eV) with atomic percentage of 74.49% and C-Si (~283.3) with atomic percentage of 24.51%, respectively [73].…”
Section: Surface Characteristics Of the Synthesized Silica Nanosheetsmentioning
confidence: 99%
“…Even though, graphene have been used extensively as adsorbent for many biomedical applications due to its unique properties and apparent biocompatibility [38][39][40][41], graphene has poor hydrophilicity that often requires the surface to be modified with hydrophilic moieties prior to its application [42][43][44]. Thus, mesoporous graphene-like multilayer silica nanosheets are emerging as an attractive alternate material for biomedical applications due to their unique and desirable features, such as high surface area, narrow size distribution, uniform dispersion, chemical stability, hydrophilicity, biocompatibility and high selectivity towards many molecules like peptides [12,22,[45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…A ilustração da Figura 2.a apresenta uma partícula de ferro sendo recoberta por particulados de fosfato de estrôncio e óxido bórico. Já na Figura 2.b é possível observar o surgimento de uma fina camada de dióxido de silício recobrindo a partícula de ferro (ISHIZAKI et al, 2017). A utilização nano-filmes de sílica ou sílica coloidal sobre camadas isolantes compostas por fosfato de estrôncio e óxido bórico, de forma a conseguir camadas isolantes em partículas de ferro em pó com mais alta resistividade elétrica.…”
Section: Características Da Camada Isolanteunclassified
“…Da mesma forma, diferentes tipos de recobrimentos podem ser aplicados sobre a partículas magnéticas para formar a camada isolante, sendo divididas em camadas orgânicas e inorgânicas, metálicas e não metálicas. Camadas isolantes tratadas com ácido fosfórico (H3PO4) são descritas nos trabalhos (CHEN et al, 2020(CHEN et al, , 2019ISHIZAKI et al, 2017;MAEDA et al, 2010;XIA et al, 2019;ZHOU YE;BJORN SKARMAN, 2012), bem como a adição de algum tipo de óxido na solução (um isolante de óxido pode ser usado, além de fosfato de ferro, fosfato de manganês, fosfato de zinco, fosfato de cálcio, fosfato de alumínio, óxido de silício, óxido de alumínio), tal como óxido de titânio, ou óxido de zircônio (SOARES; ALVES, 2021).…”
Section: Introductionunclassified
“…The applications of iron powders are branched into various areas like powder metallurgy parts, 19) welding electrodes, magnetic materials, 20,21,72) electrochemical parts, 22) alkaline batteries, [23][24][25][26][27][28] food fortification, 29) environmental remediation, [30][31][32] industrial filters and purifies, 33) etc. Extremely modern and futuristic application of iron powders is targeted to use them as clean recyclable metal fuel.…”
Section: Synthesis Morphology and Applicationsmentioning
confidence: 99%